Understanding anionic Chugaev elimination in pericyclic tetracene formation. Issue 13 (31st March 2016) - Burroughs, Laurence; Ritchie, John; Woodward, Simon
Abstract: The reaction pathway for the formation of tetracenes from the diols 1, 2-C6 H4 (CHOHCCAr)2, LiHDMS, CS2 and MeI has been modelled by computational methods at the CBS-QB3 level of theory. Comparison of PhCHOC(=S)YCCPh (Y=S − or SMe) indicates a slight kinetic advantage for the anionic system towards [3, 3]-sigmatropic rearrangement [Eact (calcd) 19.7 vs 21.8 kcal mol −1 ]. Using anthracene-based models, 10-{SC(=O)Y}-4a, 10-dihydroanthracene (Y=S − or SMe), allows direct comparison of both syn and anti -manifolds in the neutral versus anionic Chugaev elimination. syn -Elimination of [HSC(=O)S] - is distinctly favoured [Eact (calcd) 11.4 kcal mol −1 ] versus syn elimination of neutral methylated HSC(=O)SMe [Eact (calcd) 27.5 kcal mol −1 ]. The smaller barrier to syn elimination of the anionic leaving group is in accord with the low temperature conditions required for this Chugaev reaction (60 °C) and suggests a general advantage in carrying out Chugaev eliminations in anionic manifolds. Graphical abstract: